Unveiling the Dynamics of Reverse Passing and Transracialism: Navigating Identity and Authenticity - Zahra Ines GAFOUR (Langues & Cultures)
In the discourse of identity and cultural appropriation, reverse passing and transracialism have emerged as complex phenomena. Reverse passing involves individuals adopting the identity of another racial or cultural group, challenging conventional notions of authenticity. Transracialism describes individuals identifying with a race different from their birth assignment, highlighting the fluidity of racial identity. This study explores these phenomena through the lens of case studies, media content analysis, and scholarly literature, aiming to uncover the motivations behind reverse passing and transracialism. By exploring the intersections of identity formation, cultural appropriation, and power dynamics, this research offers a deeper insight into the complexities of race, identity, and societal perceptions in the contemporary world.